Achievement Motives of North Sumatra Athletics Team in Facing Competitions - Ravsamjani, Faridz; Ginting, Alin Anggreni; Handoko, Abdul Harris (ACPES Journal of Physical Education, Sport, and Health (AJPESH), 2024)
This study aims to analyze the achievement motive factors of North Sumatra Athletics athletes in facing competitions. The subjects in this study were 28 people. This research is included in quantitative research. The data analysis technique used is descriptive statistics with the formula F percent, which is used to determine the percentage of athletes and the frequency of answers for each factor. Considering the relatively small population, this research uses the entire population as the sample in this research. The data collection method used in this research is by using a scale. The scale model used is the Likert scale. Based on the results of data analysis, from the scale of achievement motives seen from the characteristics 1) Characteristics of self-confidence and responsibility, there were 82.14% who stated that they had a sense of self-confidence and responsibility. 2) Characteristics of having a future orientation, there are 89.2% who have a future orientation. 3) Characteristics of having a high urge to act. There are 92.8% who have a high urge to act. 4) Characteristics of having creativity: It turns out that 75% have creativity. 5) Characteristics of having tough friends. It is known that 82.14% have tough friends. 6) Open nature turns out there are 89.2% who have open nature.